2010
DOI: 10.1108/20401461011049520
|View full text |Cite
|
Sign up to set email alerts
|

Lean implementation and its benefits to production industry

Abstract: PurposeThe purpose of this paper is to discuss the lean implementation process and its quantified benefits for the production industry with the help of value stream mapping (VSM). Both current and future state maps of the organization's shop floor scenarios are discussed using VSM techniques in order to highlight improvement areas and to bridge the gap between the existing state and the proposed state of shop floor of the selected industry.Design/methodology/approachVSM process symbols are used to discuss lean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 30 publications
4
101
0
11
Order By: Relevance
“…Bhasin (2011) and Singh et al (2010) reported about lean implementation for production companies however the cost benefit or financial aspects are still missing. Lu et al(2011) remarked the difficulty to compare future value chain structures on effectiveness indicating it would be of interest to have methods and tools to test these future value chain structures.…”
Section: Lean Implementation In the Industrymentioning
confidence: 99%
“…Bhasin (2011) and Singh et al (2010) reported about lean implementation for production companies however the cost benefit or financial aspects are still missing. Lu et al(2011) remarked the difficulty to compare future value chain structures on effectiveness indicating it would be of interest to have methods and tools to test these future value chain structures.…”
Section: Lean Implementation In the Industrymentioning
confidence: 99%
“…Kaizen is a Japanese word that essentially means "change for the better" or "good change" [3,5,7,8,13]. The goal is to provide the customer with a defect free product or service when it is needed and in the quantity it is needed.…”
Section: Enactment Of Lean In Ethiopia Plastic Industrymentioning
confidence: 99%
“…The best answer as found in most of the journals is lean manufacturing. Lean manufacturing helps in enhancing production processes and boosting up the employees job satisfaction [3].…”
Section: Introductionmentioning
confidence: 99%
“…So, the use of this approach was widely accepted by the firms who were already employed the TPS (Liker, 2004). Lean Principles were developed for imparting the flexibility in the mass production by eliminating the wastages (Sohal, 1996;Guliyani, 2001;Shah & Ward, 2003;Singh et al, 2010). The identification of wastages (refers to non-value added activities) and eliminating them are the tough tasks for all the organizations (Karlsson & Ahlstrom, 1996;Sanchez & Perez, 2001;Hines et al, 2004;Moayad & Shell, 2009).…”
Section: Introductionmentioning
confidence: 99%